The Effect of Sugar Solution Concentration on Characteristics of Candied Dried Tomatoes (Solanum lycopersicum L.) - Ida Ningrumsari; Moch Alhikam Afrijal R; Rimba Tsania Nurulhusna (International Journal of Quantitative Research and Modeling, 2023)
Tomatoes are a type of food that has high production and is a perishable food. In addition, the utilization of processed tomatoes as a food source is still not optimal. So, it is necessary to do the right food processing on tomatoes, one of which is processed into dried candied. The purpose of this study was to determine the concentration of sugar solution, so as to produce dried candied with good characteristics. The research was conducted at the Chemistry Laboratory and Food Processing Laboratory, Faculty of Agriculture, Ma'soem University from May to July 2022. The method used is the old experimental method, namely the Randomized Block Design (RBD) consisting of 6 (six) treatments and each repeated 4 (four) times. The treatments given were concentration A (40%), B (45%), C (50%), D (55%), E (60%), F (65%). The analysis in this study included water content, total dissolved solids. Meanwhile, organoleptic testing was carried out on the color, aroma, taste, and hardness of the dried candied produced. The results showed that the concentration of sugar solution had a significant effect on water content, total dissolved solids, and organoleptic properties. Only partially significant influenced the organoleptic properties of the dried candied produced. The results of the study can be concluded that the concentration of 55% sugar solution produces good characteristics of candied dried tomatoes, this determination is based on the level of color preference of 3.97, aroma of 4.38 and taste of 4.48 from a maximum value of 5.00, moisture content of 9.04% and total dissolved solids content of 62.80%.